The multi-density integral equation approach in the theory of complex liquids - Holovko, M.F. (Condensed Matter Physics, 1999)
Recent development of the multi-density integral equation approach and its application to the statistical mechanical modelling of a different type of association and clusterization in liquids are reviewed. The effects of pairing, polymerization, solvation, formation of the network bonds and self- assembling are discussed. The numerical and analytical solutions of the integral equations in the multi-density formalism are used for the description of the association phenomena in the electrolyte and polyelectrolyte solutions, water, polymers, microemulsions and other ﬂuids. The application of the multi-density integral equation approach for the treatment of the percolation phenomena, the adsorption of ﬂuids in porous media and the description of electronic structure of associative ﬂuids are illustrated. Подається огляд наближення багатогустинних інтегральних рівнянь і їх застосування для опису асоціації та кластеризації в рідинах. Обговорюються ефекти спарювання, полімеризації, сольватації, утворення сітки зв’язків та самоасоціації. Для опису асоціативних явищ в електролітичних та поліелектролітичних розчинах, воді, полімерах, мікроемульсіях та інших рідинах використовуються чисельні та аналітичні розв’язки інтегральних рівнянь в багатогустинному формалізмі. Ілюструються застосування наближення багатогустинних інтегральних рівнянь для опису перколяційних явищ, адсорбції рідин в пористих середовищах та опису електронної структури асоціативних рідин.